PERBEDAAN TEKNIK RELAKSASI DAN TERAPI MUSIK KLASIK TERHADAP PENURUNAN SKALA NYERI PADA PASIEN SECTIO CAESAREA - Linda Suryani; Husna Farianti Amran (LPPM Universitas Abdurrab, 2025)
The number of births via Caesarean section continues to rise worldwide. Caesarean births have a five-fold higher risk of complications compared to normal births. One of the problems that arise after a Caesarean section is severe pain in the surgical wound. Post-Caesarean pain management can be done pharmacologically and non-pharmacologically. Non-pharmacological methods include deep breathing relaxation and classical music. These two techniques are able to significantly reduce pain intensity. This study aims to compare between relaxation techniques and classical music therapy in an effort to reduce pain levels in patients undergoing Caesarean section at Permata Hati Duri Hospital. This study uses a quasi-experimental method with a pre-test and post-test research design. The sample size in the study was 74 respondents, divided into 37 respondents using deep breathing relaxation techniques and 37 respondents using classical music techniques. Sample selection was done using purposive sampling. The research instrument used the Wong-Baker face rating scale with a scale of 0-10. Data analysis used the Wilcoxon test, while to compare between the two techniques, the Mann-Whitney test was used. The results showed that there was a difference in pain scale between before and after the intervention, both using deep breathing relaxation techniques and using classical music with a P-value of 0.000. To see the difference in the decrease in pain scale using deep breathing relaxation techniques or using classical music, the results showed that there was no difference in the decrease in pain scale after therapy using deep breathing relaxation techniques and classical music in post-Caesarean section patients. It is hoped that deep breathing relaxation techniques and classical music can be an effective approach to alleviate pain in mothers after Caesarean section